2019
DOI: 10.1177/0300985818823669
|View full text |Cite
|
Sign up to set email alerts
|

A Transplantable Syngeneic Allograft Mouse Model for Nongestational Choriocarcinoma of the Ovary

Abstract: Nongestational choriocarcinoma is a rare malignancy in humans with poor prognosis. Naturally occurring choriocarcinoma is also rare in laboratory mice, and no genetic mouse model accurately recapitulates the features of this cancer. Here we report development of a genetically engineered mouse (GEM) model with alterations in Brca2, Trp53, and RB that develops ovarian tumors. Most of the ovarian tumors displayed histological characteristics of nongestational choriocarcinoma of the ovary (NGCO) (47%) with abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…One study compared the genetic molecular biology of GOC and NGOC, and found mutations involving DNAJB9, a negative feedback regulator of p53 and NGOC cells showing aberrant expression of p53 [18]. Genetically engineered mouse models with alterations in Trp53 gene were also shown to develop NGOC [19]. NGOC cells have also demonstrated copy number variations and significant amplification of Her2, IKZF3, PGAP3, and C-Myc, which are not demonstrated by GOC; these genes have been implicated in the poorer immunogenicity of NGOC, thus resulting in less sensitivity to chemotherapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…One study compared the genetic molecular biology of GOC and NGOC, and found mutations involving DNAJB9, a negative feedback regulator of p53 and NGOC cells showing aberrant expression of p53 [18]. Genetically engineered mouse models with alterations in Trp53 gene were also shown to develop NGOC [19]. NGOC cells have also demonstrated copy number variations and significant amplification of Her2, IKZF3, PGAP3, and C-Myc, which are not demonstrated by GOC; these genes have been implicated in the poorer immunogenicity of NGOC, thus resulting in less sensitivity to chemotherapy [12].…”
Section: Introductionmentioning
confidence: 99%